IMPLEMENTASI APLIKASI SIMBA DI KANTOR BAZNAS KOTA BUKITTINGGI - Hergiansyah Hergiansyah; Syamsir Syamsir; Puji Dwi Putra; Tyara Febrila; Wahyu Yendra (Universitas Palangka Raya, 2022)
Along with the progress of the Digitalization Era, people's needs are increasingly complex so that they must be followed by optimizing excellent public services and one of the ways that must be carried out by the state apparatus is by utilizing information technology or also known as Public Information System Management. According to the Law of the Republic of Indonesia Number 23 of 2011 concerning Zakat Management, chapter I article 1 paragraph 7 states that the National Zakat Amil Agency, hereinafter referred to as BAZNAS, is an institution that manages zakat nationally. Furthermore, in Chapter II article 5 paragraphs 1, 2 and 3 it is stated that to carry out zakat management, the Government establishes BAZNAS domiciled in the State capital which is a non-structural government institution that is independent and responsible to the President through the Minister. SIMBA can be used by BAZNAS throughout Indonesia as an operational standard for zakat institutions and national zakat reporting. SIMBA or BAZNAS Information Management System is a system that is a new breakthrough in terms of fulfilling the role of the national zakat coordinator for the creation of a transparent and accountable zakat management system throughout Indonesia. With an online basis, the role of the zakat coordinator can reach almost all parts of Indonesia. However, the implementation of SiMBA did not go smoothly, there was a lot of zakat data that had to be recorded starting from registration, receipt and distribution of zakat, causing various problems, namely data loss, so designing a web-based zakat management information system is one way to overcome the problems and weaknesses of the process. zakat management.